Topographical orientation effects on friction and wear in sliding DLC and steel contacts, part 1: Experimental - Holmberg, K.; Laukkanen, A.; Ronkainen, H.; Waudby, R.; Stachowiak, Gwidon; Wolski, M.; Podsiadlo, P.; Gee, M.; Nunn, J.; Gachot, C.; Li, L. (Elsevier Ltd, 2015)
The effect of surface roughness and topographical orientation on friction and wear has been investigated for diamond like carbon (DLC) coated and uncoated steel surfaces with three levels of surface roughness in the range of 0.004–0.11 μm Ra value and with topographical orientations at 0°, 45° and 90° angles from grinding marks. In this first part we report the experimental observations that form the basis for future computational modelling of the tribological effects and mechanisms. The surfaces were characterised by the scanning electron microscopy (SEM) and focused ion beam (FIB) method and mechanical properties were measured. In the topographical characterisation measurements included the fractal signatures, the texture aspect ratio signatures and the texture direction signatures were measured and calculated by the variance orientation transform (VOT) method. The friction and wear were measured and observed in scratch testing, micro tribological testing and linear reciprocating testing in three directions of topographical orientation, as well as in rotational pin-on-disc testing. The topographical orientation had considerable effect on both friction and wear in DLC vs DLC contacts while the effect was minor and sometimes not even observable in steel vs steel contacts. A surface strengthening effect which is higher for smooth DLC surfaces and micro-cracking and micro-delamination on asperity tips at low loads for rougher surfaces is reported. The 45° orientation resulted in higher friction and considerably higher ball wear in linear reciprocating pin-on-plate testing of DLC surfaces compared with the 0° and 90° orientations.